Explaining confidence in the police within transitional Hong Kong: the influence of postmaterial values - McCarthy, Daniel (Policing and society, 2023)
The Hong Kong Police Force (HKPF) has a tradition for being among the most respected national police organisations globally. More recent political events in Hong Kong have however placed the HKPF in highly visible public order situations. A wide array of political factions have emerged as a consequence of the handover of control in Hong Kong, many of which have involved young people protesting the curtailment of democratic rights. In this paper, we utilise Wave 7 of the World Values Survey (n = 2075). We utilise Inglehart’s (1971. The silent revolution in Europe: intergenerational change in post-industrial societies. American political science review, 65 (4), 991–1017) concept of postmaterialism to examine how far young people’s more negative attitudes to the police can be underpinned by cohort-based (or generational) explanations. Our findings identify associations between postmaterialist values and lower confidence in the police. Those that favoured stricter immigration controls, experienced higher fear of crime, perceived drug selling in their area, and consumed certain types of media (notably television and new media) were also less likely to have confidence in the HKPF.